2014
DOI: 10.1242/dev.108415
|View full text |Cite
|
Sign up to set email alerts
|

Simplet/Fam53b is required for Wnt signal transduction by regulating β-catenin nuclear localization

Abstract: Canonical β-catenin-dependent Wnt signal transduction is important for several biological phenomena, such as cell fate determination, cell proliferation, stem cell maintenance and anterior-posterior axis formation. The hallmark of canonical Wnt signaling is the translocation of β-catenin into the nucleus where it activates gene transcription. However, the mechanisms regulating β-catenin nuclear localization are poorly understood. We show that Simplet/ Fam53B (Smp) is required for Wnt signaling by positively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 69 publications
1
28
0
Order By: Relevance
“…The comparison with eQTL data sets revealed a colocalization of MPB-risk variants with known regulatory variants ( r 2 >0.5 between eQTL single nucleotide polymorphism (SNP) and MPB lead SNP) in 25 loci. For 10 of these 25 loci, previous studies have found an association between the MPB lead SNP itself and gene expression for example, of CRHR1 , which encodes for a receptor for corticotropin releasing hormone (CRH), a known hair growth inhibitor and catagen inductor17, FAM53B a positive regulator of WNT/beta-catenin-signalling18 and other genes, for example, ANXA2 , SUCNR1 , WARS2 that have not yet been associated with hair biology (Supplementary Table 2). Detailed functional follow-up studies are now warranted to confirm these regulatory interactions, and to investigate the contribution of these candidate genes to the development of key MPB pathophysiological signs.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison with eQTL data sets revealed a colocalization of MPB-risk variants with known regulatory variants ( r 2 >0.5 between eQTL single nucleotide polymorphism (SNP) and MPB lead SNP) in 25 loci. For 10 of these 25 loci, previous studies have found an association between the MPB lead SNP itself and gene expression for example, of CRHR1 , which encodes for a receptor for corticotropin releasing hormone (CRH), a known hair growth inhibitor and catagen inductor17, FAM53B a positive regulator of WNT/beta-catenin-signalling18 and other genes, for example, ANXA2 , SUCNR1 , WARS2 that have not yet been associated with hair biology (Supplementary Table 2). Detailed functional follow-up studies are now warranted to confirm these regulatory interactions, and to investigate the contribution of these candidate genes to the development of key MPB pathophysiological signs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Wnt signaling has been implicated in kidney development and disease 24 . FAM53B controls βcatenin nuclear localization 25 , a key component of Wnt signaling. β-catenin translocation into the nucleus allows for activation of target genes via interaction with TCF transcription factors 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…The best-known member of the family is FAM53B, a controller of tissue development and cell proliferation [33, 37]. FAM53B is required for Wnt signaling, a pathway involved in epithelial-to-mesenchymal transition and subsequent metastasis in breast cancer [3840]. FAM53B has also been identified as a critical gene in the prognosis of multiple myeloma in a transcriptional network analysis [41].…”
Section: Discussionmentioning
confidence: 99%